Challenges and strategic directions in pediatric nursing clinical practicum in South Korea: a descriptive study. - Shim, Ka Ka; Ji, Eun Sun (Child Health Nursing Research, 2026)
Purpose: This study aimed to examine the current status and key challenges of pediatric nursing clinical education in South Korea and to provide strategic directions for quality improvement based on competency-based learning outcomes. Methods: A cross-sectional survey was conducted among 89 pediatric nursing faculty members working at various universities nationwide between February and July 2024. Quantitative data were analyzed using descriptive statistics, and qualitative responses were analyzed using inductive content analysis. Results: Practicum objectives primarily focused on inpatient care (98.9%) and core nursing skills (83.1%), while communication and problem-solving (22.4%) and ethics (21.3%) were underrepresented. Although high-fidelity simulation use reached 33.7%, interactive tools such as virtual reality (17.9%) and nursing process evaluations (7.8%) remained underutilized. Six themes emerged from the analysis of faculty perspectives on enhancing clinical practicum education: structural barriers in securing sites, inconsistent learning environments, overcrowding, limitations of observation-only learning, regulatory constraints, and excessive faculty burden. Conclusion: This study proposes establishing standardized clinical protocols, expanding hybrid simulation-based models to compensate for shrinking clinical sites, and institutionalizing industry-academic cooperative frameworks to ensure the quality and equity of pediatric nursing education. These approaches are essential to enhancing the quality and equity of pediatric clinical nursing education in Korea.